Analisis Strategi Bisnis pada Pabrik Tahu Mbah Djoyo - Rostiana Rostiana; Sadjiarto Sadjiarto; Destri Sambara Sitorus (Universitas Sebelas Maret, 2025)
Economic growth in the current era of globalization can be seen with the development of the business world in various fields. One of the efforts to support economic growth is by developing the Micro, Small and Medium Enterprises (MSME) sector. The role of MSMEs in Indonesia is very important, namely for the distribution of the population's economy and supporting the country's economic development. This study aims to determine the business strategy used by Mbah Djoyo Tofu Factory SMEs in developing their business. The business strategy includes production strategy and marketing strategy. The research approach used is a qualitative approach using descriptive analysis. The results of this study found that the business strategies carried out by Mbah Djoyo's Tofu Factory SMEs in developing their business included production and marketing strategies. The production strategy contributes well to the development of Mbah Djoyo's tofu factory SMEs as evidenced from the production stages, namely by selecting quality raw materials, using adequate production equipment to help the production process run effectively, minimizing production costs by using diesel engines and carrying out quality and supervision in the production process. production. However, there are still obstacles in the production strategy, namely limitations in obtaining husk fuel. While the marketing strategy of this business sells its products using a personal selling strategy and a humanistic approach. This is an obstacle in promoting its products because it is still carried out in a limited manner by relying on personal selling techniques and relationships with the community so that the marketing carried out is less effective.Keywords: business strategy, marketing, production, MSME